THE EFFECT OF EMOTIONAL INTELLIGENCE, SPIRITUAL INTELLIGENCE AND LEARNING BEHAVIOR ON THE LEVEL OF ACCOUNTING UNDERSTANDING - Nur Eliza; Diah Amalia (Pusat P2M Politeknik Negeri Batam, 2022)
This study aims to determine whether there is an influence between emotional intelligence, spiritual intelligence and learning behavior on the level of accounting understanding . This accounting understanding is measured by grades in introductory accounting courses, intermediate financial accounting, advanced financial accounting . Emotional intelligence in this study was measured using self-knowledge, motivation, empathy, social skills. Spiritual intelligence was measured using being flexible, dealing with and overcoming pain, aversion to causing harm and being independent. Learning behavior was measured using the habit of following lessons, reading books, visiting the library, and taking exams. This research uses non probability sampling method with purposive sampling technique . The data processing technique uses SPSS 2 0 by performing multiple regression tests. This study uses a questionnaire distributed via google form with the number of respondents as many as 104 Batam State Polytechnic students. The results found that, firstly, emotional intelligence has a positive influence on accounting understanding . Second, spiritual intelligence has a positive influence on accounting understanding. Third, learning behavior has a positive influence on accounting understanding.